Synthesis of Ni nanowires via a hydrazine reduction route in aqueous ethanol solutions assisted by external magnetic fields - Zhang, Liying; Wang, Jian; Wei, Liangming; Liu, Ping; Wei, Hao; Zhang, Yafei (Nano-Micro Letters, 2009)
One-dimensional Ni nanostructures were synthesized via a hydrazine reduction route under external magnetic fields. The mixture of de-ionized water and ethanol was used as the reaction solvent and hydrazine hydrate as reducing agents. The morphology and properties of Ni nanostructures were characterized by X-ray diffractometer (XRD), scanning electron microscopy (SEM), and vibrating sample magnetometer (VSM). It was found that the magnetic field strength, concentration of Ni ions, reaction time and temperature as well as pH values played key roles on formation, microstructures and magnetic properties of Ni nanowires. The optimal wires have diameter of ∼200 nm and length up to ∼200 μm. And their coercivity is ∼260 Oe, which is much larger than the commercial Ni powders of 31 Oe. This work presents a simple, low-cost, environment-friendly and large-scale production approach to fabricate one-dimensional magnetic materials. The resulting materials may have potential applications in conductive filters, magnetic sensors and catalytic agents.